2012
DOI: 10.1111/j.1439-0426.2012.02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-seasonal persistence and size-structuring of two minnow species within headwater streams in the Eastern Cape, South Africa

Abstract: Summary This study examined temporal variation in population dynamics and size structuring of two cyprinid minnows, Pseudobarbus afer and Barbus anoplus, in relation to their proximate physical habitats. Population estimates were determined using three‐pass depletion sampling during both summer and winter. The habitats were characterised by seasonal variation in all physico‐chemical conditions and spatial variation in substrata compositions. Whereas significant differences in population size were noted between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This is one of the first demonstrations of this phenomenon for African fishes, one other concerning the aquaculture of African sharptooth catfish Clarias gariepinus (Burchell 1822) (van de Nieuwegiessen et al ., ), although presumably many other African fishes possess such chemicals. The main response was to dart to shelter, which corresponds with their preferred habitat type (Kadye & Booth, , ) and the normal behaviour shown in this study. However, contrary to predictions, redfins reduced the time they spent motionless in response to alarm cues.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This is one of the first demonstrations of this phenomenon for African fishes, one other concerning the aquaculture of African sharptooth catfish Clarias gariepinus (Burchell 1822) (van de Nieuwegiessen et al ., ), although presumably many other African fishes possess such chemicals. The main response was to dart to shelter, which corresponds with their preferred habitat type (Kadye & Booth, , ) and the normal behaviour shown in this study. However, contrary to predictions, redfins reduced the time they spent motionless in response to alarm cues.…”
Section: Discussionsupporting
confidence: 68%
“…The consequently reduced distribution of P. afer sensu stricto suggests its conservation status may be underestimated. Redfins would therefore benefit from conservation of existing populations (Kadye & Booth, , ; Chakona & Skelton, ) and assisted reintroduction. However, it is also under threat from invasion by novel predators (Ellender et al ., ; Ellender & Weyl, ; Kadye & Booth, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies elsewhere have shown that lower reaches of rivers are characterised by high richness that is mediated by trophic diversification that allows different fishes to occupy different trophic positions (Guo et al, ; Ou et al, ). Secondly, the general absence in the Great Fish River's upper mainstem section of the E. anoplus , which was historically widespread (Laurenson & Hocutt, ), suggest the likely impact of the IBWT in influencing both habitat availability for this species, together with the proliferation of multiple non‐native fishes, which include generalist predators such as C. gariepinus (Kadye & Booth, , ).…”
Section: Discussionmentioning
confidence: 99%